2008
DOI: 10.1128/aac.01311-07
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Humoral Immunity Is Critical for Successful Antiviral Therapy in Disseminated Mouse Adenovirus Type 1 Infection

Abstract: Severe adenovirus infections in transplant recipients undergoing immunosuppressive therapy are of increasing concern. Controversy exists on the contribution of antiviral therapy and the host immune response to recovery from these infections. Here, we established a systemic mouse adenovirus type 1 (MAV-1) infection in cyclophosphamide (CyP)-treated BALB/c mice. CyP was administered at 100 mg per kg of body weight every other day for 2, 3, or 4 weeks, thereby inducing general but reversible leukopenia, with a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In SCID mice, continued cidofovir therapy caused a marked delay in, but could not prevent fatal MAV-1-induced disease, suggesting the indispensability of an efficient host immune response for complete viral clearance [145]. This was confirmed by the positive effect of anti-MAV-1-specific IgG therapy, and by antiviral treatment of MAV-1-infected mice experiencing cyclophosphamide-induced immunosuppression [146], as the effect of cidofovir therapy depended on the level of immunosuppression. In particular, recovery of humoral immunity seemed to be critical for successful antiviral therapy in disseminated MAV-1 infection.…”
Section: Animal Models For Adenovirus Infectionmentioning
confidence: 98%
“…In SCID mice, continued cidofovir therapy caused a marked delay in, but could not prevent fatal MAV-1-induced disease, suggesting the indispensability of an efficient host immune response for complete viral clearance [145]. This was confirmed by the positive effect of anti-MAV-1-specific IgG therapy, and by antiviral treatment of MAV-1-infected mice experiencing cyclophosphamide-induced immunosuppression [146], as the effect of cidofovir therapy depended on the level of immunosuppression. In particular, recovery of humoral immunity seemed to be critical for successful antiviral therapy in disseminated MAV-1 infection.…”
Section: Animal Models For Adenovirus Infectionmentioning
confidence: 98%
“…Antibody preparations, including polyclonal immunoglobulin with high-titers against RSV (Respigam, MedImmune, Inc. Gaithersburg, MD, USA), have been used in a few cases. Though these agents have biologic plausibility (45), their benefit is unclear (CIII) (29). Enhancement of adenovirus-specific immunity, through lymphocyte infusion, may improve outcomes in disseminated infections but this intervention has not been studied in the solid organ population (46,47).…”
Section: Treatmentmentioning
confidence: 99%
“…Also, some reports noted that prophylactic treatment of transplant patients with GCV to prevent CMV infection seemed to decrease the incidence of Ad infections (30)(31)(32). Several case studies suggested that GCV used therapeutically in transplant patients has anti-Ad activity (33)(34)(35).…”
mentioning
confidence: 99%